Pengaruh Terpaan Trailer Film Joker Terhadap Keputusan Remaja Untuk Menonton Film Joker Di Bioskop - Savarino, Jocelyn Williams; Pradipta, Ade Devia; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2020)
ABSTRACT The success of Joker film's gross income about 1,073,151,773 cannot be separated from the effort by the production house Warner Bross Pictures to promotes joker film by giving a trailer view on all kind of media platform including social media and some conventional media. The goal of this research is to find about how Joker's trailers affect the teenager's decision to watching the